2014
DOI: 10.1039/c4md00245h
|View full text |Cite
|
Sign up to set email alerts
|

Pyrido- and benzisothiazolones as inhibitors of histone acetyltransferases (HATs)

Abstract: Histone acetyltransferases (HATs) are interesting targets for the treatment of cancer and HIV infections but reports on selective inhibitors are very limited. Here we report structure-activity studies of pyrido-and benzisothiazolones in the in vitro inhibition of histone acetyltransferases, namely PCAF, CBP, Gcn5 and p300 using a heterogeneous assay with antibody mediated quantitation of the acetylation of a peptidic substrate. Dependent on the chemical structure distinct subtype selectivity profiles can be ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Nevertheless, growth inhibition in prostate cancer cells (LNCaP, GI50 ~36-37 µM) as well as leukemic cells (HL-60, GI50 ~3-4 µM) was elicited to the same extent [113]. was further used as a tool compound to decipher the differential roles of CBP and p300 in TCF/β-catenin-mediated survivin gene expression [122].…”
Section: Pyridoisothiazolones Pu139 -Pan-hat and Pu141 -P300/cbpmentioning
confidence: 99%
“…Nevertheless, growth inhibition in prostate cancer cells (LNCaP, GI50 ~36-37 µM) as well as leukemic cells (HL-60, GI50 ~3-4 µM) was elicited to the same extent [113]. was further used as a tool compound to decipher the differential roles of CBP and p300 in TCF/β-catenin-mediated survivin gene expression [122].…”
Section: Pyridoisothiazolones Pu139 -Pan-hat and Pu141 -P300/cbpmentioning
confidence: 99%
“…N-Aryl substituted compounds were shown to cause pan-KAT inhibition on a series of enzymes (PCAF, Gcn5, p300, CBP, and MOF), while N-benzyl or N-alkyl substituents led to defined subtype selectivity patterns. 137 The Fantappie group incubated Schistosoma mansoni parasites with the compound 12.2 (PU139) and reported impaired promoter activity of the egg shell protein Smp14, probably evidently as a result of diminished SmGCN5 and SmCBP1 activity. 138 The repression of Smp14 controlled gene products led to production of abnormal and defective eggs, implying KAT inhibition as novel strategy in the control of schistosomiasis.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Structure–activity studies revealed a crucial role of the substituent in 2-position for inhibitory activity. N -Aryl substituted compounds were shown to cause pan-KAT inhibition on a series of enzymes (PCAF, Gcn5, p300, CBP, and MOF), while N -benzyl or N -alkyl substituents led to defined subtype selectivity patterns . The Fantappie group incubated Schistosoma mansoni parasites with the compound 12.2 (PU139) and reported impaired promoter activity of the egg shell protein Smp14, probably evidently as a result of diminished SmGCN5 and SmCBP1 activity .…”
Section: Kat Modulatorsmentioning
confidence: 99%
“…Certainly continued vigilance will be required as BITZ compounds and their derivatives progress in development, with continued monitoring for potential promiscuous and off-target reactivity that may lead to toxicity. However, it should be noted that, similar BITZ chemotypes have demonstrated successful medicinal chemistry optimisation36373839404142. Recently, a molecule containing a BITZ moiety has begun Phase II clinical trials as an antiviral agent, providing important evidence that the potential reactivity of the BITZ moiety alone is not incompatible with a safe therapeutic profile43.…”
Section: Discussionmentioning
confidence: 99%